Value Chain analysis of the mining industries in Peru - Aguirre Alván, Luis (2025)
Mining is considered the central economic activity in Peru, as its industry is essential for its social and economic development, contributing significantly to GDP and generating formal employment. Despite its benefits, it faces several challenges, which require transparent resource management. Integrating the value chain of the extractive industries and promoting sustainability policies are key to maximizing the advantages of the mining industries and minimizing negative impacts.